WHO MOVES WESTERN EUROPE STOCK MARKETS? - Setiadi, Robertus (Directorate of Academic Research and Community Services, 2020)
This paper focuses on short- and long-term causal relationship on six major Stock Exchanges in Western Europe which actively traded, while also considering the interaction with US Stock Exchange. The observation period is separated into 3 sub-samples to represent the pre-crisis period, crisis period, and post-crisis period; while the author also distinguishes between local currency and USD denominations in stock closing price. Conversion of local currency in USD denominations shows an effect on increasing the inter-dependence shown in the pre-crisis observation while tested using Johansen test. In the whole-period sample, Belgium, Germany, and the US should be considered as dominant country to granger cause the other Western Europe. Long-term relationships were also tested by granger causality showing different characteristics in each sub-sample. Finally, Italy is the most sensitive country in the response to other Western European countries innovations while tested by Generalized Impulse Response Analysis.